PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PENGUASAAN KONSEP IPA FISIKA - Fatmawati, Mega; Lumbu, Albert; Walukow, Auldry F. (Papua Journal of Physics Education, 2023)
Research has been carried out with the aim of knowing (1) increasing mastery of students' concepts by using PBL learning models, (2) differences in students' mastery of conceptual understanding between the use of PBL learning models and direct learning, (3) differences in students' critical thinking abilities between uses problem based learning model and direct learning. The method of this research is quantitative research, with quasy experimental. The experimental design used was nonequivalent pretest-posttest control group design. The population of 178 students is class VIII semester II Muhammadiyah Middle School Jayapura Academic Year 2018/2019. The sample used is class VIII D and VIII E with a total sample of 72 students. Sampling is used non probability sampling technique by means of purposive sampling. Mastery concept data was collected through pretest and posttest and critical thinking ability data were collected through posttest. The instruments used were mastery test concepts in the form of multiple choices and tests of critical thinking skills in the form of reasoned multiple choice which have been tested for validity, reliability, degree of difficulty, and differentiation. To find out the increase in mastery of students' concepts, N-gain is used. To see differences in the increase in mastery of concepts and differences in students' critical thinking skills taught with PBL models and DI models, statistical analyzes of different tests were conducted (t-test). The results showed that (1) learning with the PBL model can improve mastery of the concept of experimental class students with a moderate category of 0.67 and a control class of 0.55 (2) there are differences in the increase in mastery of concepts between the experimental class and the control class shown significance value a <0.05 which is equal to 0,000. (3) there are differences in critical thinking skills between the experimental class and the control class which are shown to be of significance value a <0.05, which is equal to 0.001.